2013
DOI: 10.1016/j.enpol.2012.12.041
|View full text |Cite
|
Sign up to set email alerts
|

The impact of attribute preferences on adoption timing: The case of photo-voltaic (PV) solar cells for household electricity generation

Abstract: We are concerned with micro-generation, individual households generating electricity using a renewable energy technology. We focus on modelling the adoption probability of photovoltaic solar panels by a household. Using data collected from an area of Canada where a generous feed-in tariff is available to households generating electricity from solar panels, we measure household level preferences for panels and use these preferences along with household characteristics to predict adoption time intentions. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 47 publications
4
40
0
Order By: Relevance
“…In addition to system type, we found that system characteristics have a significant effect on choices. Our results show the importance of investment and operating costs and are consistent with the findings of earlier studies [12], [13], [15], [83], [84], that have emphasized the relevance of economic factors in the choice of heating system and microgeneration technology. Environmental factors have generally played an important role in choices as well.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to system type, we found that system characteristics have a significant effect on choices. Our results show the importance of investment and operating costs and are consistent with the findings of earlier studies [12], [13], [15], [83], [84], that have emphasized the relevance of economic factors in the choice of heating system and microgeneration technology. Environmental factors have generally played an important role in choices as well.…”
Section: Discussionsupporting
confidence: 81%
“…Establishing an early adopter customer base creates visibility that functions as a catalyst for diffusion in rural markets [39]. In Canada, Islam and Meade [49] argue that there should be education campaigns to communicate more information regarding the investment in PV systems, its environmental effect, and the feed-in-tariff. Otherwise, the barrier of low technology awareness cannot be overcome.…”
Section: Management Barriersmentioning
confidence: 99%
“…Endogenous factors such as technology awareness and desire for energy conservation, together with exogenous factors in the form of costs; regulatory and market structures as well as characteristics of the technology affect the rate of diffusion of household PV panels [22]. The influence and commitment of the local government to promoting energy efficient systems is another factor that affects the readiness to adopt energy efficiency measures [5,17,24].…”
Section: Motives For Adopting Energy Efficiency Measuresmentioning
confidence: 99%
“…Factors affecting the adoption of PV in the built environment have been presented in a number of studies [20][21][22][23][24]. However, there is little on BAPV in the multi-family tenant-owner cooperative housing sector.…”
Section: Introductionmentioning
confidence: 99%